KONSEP MAT DALAM MUSIK KULINTANG TARI MILUR - Dedy Firmansyah; Awang Kautzar (Sekolah Tinggi Theologia Abdiel, 2019)
The function of kulintang music for the Komering tribe is as a supporting means to carry out the entire process of customary marriage of the Komering tribe. One of the marriage process in it there is a procession using milur dance accompanied by kulintang music. The concept of mat is a distinctive character as well as a guideline in the kulintang music game, so the writer is interested in studying the concept of mat in the komering kulintang music, especially in accompanying the milur dance. This study also analyzes the shape and structure of the kulintang music mat concept in the stages of the Komering marriage, especially in accompanying the milur dance. The analysis includes musical elements contained in the form and structure of the musical presentation such as phrases, figures and motifs. This study uses qualitative methods and data collection is done by observation, interviews, study of written data and documents. The results of this study conclude that the concept of mat in kulintang music to accompany the milur dance is a guideline for coordinating musical games so that each player can play his musical instruments correctly and appropriately. Whereas the form of kulintang music in accompanying the milur dance always begins with the concept of mat in each of its performances.